The Efficacy of Ultrasound-guided Hydrodissection at Kager’s fat pad to reduce symptom in Achilles tendinopathy patients - Saiklangdee, Tharit; Thiabratana, Parichat; Lohakitsathian, Chairit (Royal Thai Air Force Medical Gazette, 2023)
Background : Achilles tendinopathy is one of the most common cause of foot and ankle disability. Conservative treatment is recommended as many patient’s pain and function will improve such as stretching, orthotics, medication etc. However, there were many patients poorly responsive to standard management. Recently, case series study, ultrasound-guided hydrodissection at Kager’s fat-pad can produce pain relief in the Achilles tendinopathy patients. Therefore, we interested in this technique may reduce symptoms in our Achilles tendinopathy patients. Methods : The study-enrolled patients showed persistent pain for more than 3 months after to all conservative treatment in the Achilles tendon. All patients were accessed for plain film of the affected heels and document the presence or absence of calcaneal spur and other information about foot deformity). VAS and FFI-TH data were performed by patient before treatment. Evaluated complication for 1 week after ultrasound-guided hydrodissection at out patient department, VAS and FFI-TH were accessed again at this visit. Finally, 2 weeks and 4 weeks after treatment, we review VAS and FFI-TH by telephone visited. Result : Enroll of thirteen suitable candidates, 6 male (46%) and 7 female (54%) patients, the median of age was 45 years (range : 34-62). 9 patients was insertional Achilles tendinopathy (69%). Initial median VAS and FFI-TH were 5.98 and 160.77 respectively. At 1 week follow-up, the median of VAS was 5.45 that significant improvement in pain score (P-value = 0.02) but not significantly different from 2 and 4 weeks after Hydrodissetion. The median FFI-TH before intervention comparing with 1,2 and 4 weeks follow-up were significantly different (P-value = 0.03, 0.01, 0.01 in the same order). There were no adverse effect or complication event along in this study. Conclusion : From the research, we found that Ultrasound-guided Hydrodissection at Kager’s fat pad can reduce symptoms in both insertional and non-insertional Achilles tendinopathy patients at a short time period, but in 4 weeks follow-up, the outcome of foot functional score was improved.